Remediation technology inventions for soil and groundwater contamination - Muhammad Hilmi M,; Sharifah Saffinas SS,; Ummi Mirza B,; Zaleha Md Isa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The reducing quality of groundwater resulted from accidental wastes compounded with soil leaching has become the topmost health concerns. Groundwater plays an important role in provisioning central source of drinking water to humanpopulation. The extensive contamination of ground water urges for remedial actions by many to control the damage. This narrative review will attempt to present the current state of remediation technologies for soil and groundwater contamination implemented to prevent further damage to the biodiversity of surrounding ecosystem. Components of each in-situ and ex-situ technologies were examined in detail to suit the characteristics of contamination site. The discoveries of reliable in-situ remediation technology of removing contaminants are another milestone for green environment sustainability. Therefore, adequate knowledge on characteristics of contamination site, understanding of groundwater flow conditions, site assessments and contaminant transport activities are crucial for future planning remediation technologies.